MORPHOSYNTACTIC CONSTRAINTS ON ENGLISH DERIVATIONAL PROCESSES - Komiljonova Ruxshona (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: Derivational morphology plays a crucial role in the expansion of vocabulary in English by forming new words through affixation and other morphological processes. However, derivation is not governed by morphology alone; it is also constrained by syntactic principles. This article examines the morphosyntactic constraints that regulate English derivational processes, focusing on the interaction between morphology and syntax. It explores how word class, argument structure, and syntactic distribution influence the acceptability and productivity of derivational forms. The study analyzes common derivational affixes such as -ness, -ity, -ize, and -er, demonstrating that their attachment is limited by both morphological compatibility and syntactic requirements. Special attention is given to category-changing derivation and the ways in which syntactic features determine possible outputs. The article also highlights theoretical approaches from generative morphology and lexicalist frameworks to explain these constraints. By examining morphosyntactic limitations on derivation, this research contributes to a deeper understanding of word formation in English and emphasizes the importance of integrating syntactic analysis into morphological studies. The findings are particularly relevant for linguistic theory, second language acquisition, and applied linguistics.